Life and death in Trypillia times: Interdisciplinary analyses of the unique human remains from the settlement of Kosenivka, Ukraine (3700-3600 BCE). - Katharina Fuchs; Robert Hofmann; Liudmyla Shatilo; Frank Schlütz; Susanne Storch; Vladislav Chabanyuk; Wiebke Kirleis; Johannes Müller (PLoS ONE)
We present an interdisciplinary analysis of finds from the Trypillia settlement of Kosenivka, Ukraine (ca. 3700-3600 BCE, Trypillia C1-2), that links information on human, faunal, and botanical remains with archaeological data to provide exceptionally detailed insights into life and death at a giant Trypillia settlement. We obtained osteological, palaeopathological, morphological and histotaphonomic data from human bone fragments; performed carbon and nitrogen stable isotopic analysis of human and animal bone to calculate food webs; modelled newly generated radiocarbon dates to refine the site's chronology; and contextualised the finds within the phenomenon of a general lack of human remains in Early and Middle Trypillia times through a literature review. Regarding the sphere of life, the biological profile of seven identified individuals reconstructed from the highly fragmented and partially burnt bones represents a demographic cross-section of the population. We documented disease symptoms common in the Chalcolithic and two cases of perimortem cranial trauma. Furthermore, food web calculations demonstrate the large contribution of cereals to the protein component of the human diet, which is supported by dental observations. We suggest that livestock were a major manure producer for crop cultivation, while meat contributed less than 10% to the human diet. Regarding the sphere of death, multidisciplinary data suggest a deadly fire event as one probable scenario for the formation of the Kosenivka find assemblage. This could be a rare example that sheds light on household size in prehistoric times. Furthermore, it adds to the extremely small number of human bone finds in Early and Middle Trypillia sites (A-C1), preceding the shift to extramural burials in its late phase (C2) in some regions. Altogether, our results indicate the huge explanatory potential that has yet to be unlocked in the rare and often poorly preserved bioarchaeological archives of the Cucuteni-Trypillia phenomenon.